Analisis Unsur Sensualitas Dalam Iklan Televisi DODO Tahun 2013 - An-Nisa, Nur (CITRAWIRA : Journal of Advertising and Visual Communication, 2022)
Advertising is intended to communicate a message to an audience. Advertising is useful in introducing a product and attracting consumers' attention about their product so that consumers want to buy it. However, it is undeniable that in designing an advertisement to make it look attractive to the public, a brand will use a variety of interesting ways to convey its message. So that the main focus is the extent to which a company is able to account for the ethics of a message conveyed in their advertisements. DODO advertisements are considered crossing the line because they show an element of eroticism that is not good when displayed in public. The method used in this study is a qualitative descriptive analysis, this study interprets and describes the data used based on attitudes and views of the ongoing situation with the final step, namely the conclusions obtained from the results of this study.